2018
DOI: 10.1002/cyto.b.21619
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CD229 as a new alternative plasma cell gating marker in the flow cytometric immunophenotyping of monoclonal gammopathies

Abstract: CD229 is a reliable new alternative PC-gating marker in routine laboratory practice. Quantitation of PC based on CD138 expression or from samples processed for CyIgL-staining should be used with caution. © 2018 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Studies published by independent investigators have shown that CD229 was expressed by most PCs (Atanackovic et al, 2011; Tembhare et al, 2018; Yousef et al, 2015). Atanackovic et al demonstrated that CD229 was expressed on 11 myeloma cell lines, including CD138−, CD229+ cell lines (Atanackovic et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies published by independent investigators have shown that CD229 was expressed by most PCs (Atanackovic et al, 2011; Tembhare et al, 2018; Yousef et al, 2015). Atanackovic et al demonstrated that CD229 was expressed on 11 myeloma cell lines, including CD138−, CD229+ cell lines (Atanackovic et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Atanackovic et al demonstrated that CD229 was expressed on 11 myeloma cell lines, including CD138−, CD229+ cell lines (Atanackovic et al, 2011). Tembhare et al demonstrated that CD229 expression was consistently brighter on PCs when compared to other bone marrow cells and more uniformly expressed than CD138 (Tembhare et al, 2018). As CD229 is not an exclusive PC marker with a lower surface density than CD138, these authors recommended using CD229 in combination with at least one additional marker to improve the specificity of PC detection.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma cells were identified and gated as described previously (Tembhare et al, 2018). The gating strategy employed is represented in Figure 1.…”
Section: Evaluation Of Cd269 Expression In Plasma Cellsmentioning
confidence: 99%
“…To round out this section on myeloma, Prashant Tembhare and his colleagues from the Tata Memorial Center in Mumbai performed an extensive evaluation of CD229 as an alternate plasma cell gating marker in their manuscript entitled, “ Evaluation of CD229 as a new alternative plasma cell gating marker in the flow cytometric immunophenotyping of monoclonal gammopathies.” All of the strategies recommended for phenotyping plasma cells typically use CD38 and CD138 as gating parameters, however with the advent of antibody‐based therapies such as daratumumab which targets and blocks CD38 and therapies on the horizon to target CD138 alternative gating markers are required. CD138 is further compromised due to loss during sample storage and processing.…”
Section: Multiple Myelomamentioning
confidence: 99%